10th Cent. B.C.E. Benjamin History in the Southern Levant: A New Historical Scenario Drawing on Benjamin Settlement Pattern, Jerusalem Archaeology, Sheshonq I’s List, and Biblical Historiography - Lee-Sak, Yitzhak (Zeitschrift des Deutschen Palästina-Vereins, 2024)
In this study, I suggest a new historical scenario concerning the lO'h cent. B.C.E. history of Benjamin. Benjamin first enjoyed its independence from its surrounding areas in the late 11 'h cent. B.C.E.; only a part of Benjamin - south of Gibeon - was affiliated to Jerusalem-Judah during the lO'h cent. B.C.E. To propose this hypothesis, I systematically examine the following elements while critically reviewing previous scholarly works and re-examining their argumentations: 1. The Iron Age 1B /Iron Age IIA transition period settlement pattern of Benjamin based on archaeology; 2. The archaeology of Jerusalem of the time (Stepped Stone Structure and Large Stone Structure in the city of David and the remains in the Ophel, Giv'iiti Parking Lot, and Jewish Quarter); 3. The Karnak temple list of Sheshonq I's march; 4. The relevant Biblical accounts about the reigns of Saul, David, and Solomon, as well as the Jeroboam- Rehoboam strife, dating to that period and related to Benjamin. The analysis of JO'h cent. B.C.E. Benjamin history demonstrates that both FINKELSTEIN's argument (the entire area of Benjamin was part of Northern Israel) and NA' AMANISERGI/NIEMANN's claim (it was part of Jerusalem-Judah) should be equally criticized.